DAMPAK MODEL PICTURE AND PICTURE TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Marus, Ali; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the impact of the Picture and Picture model on student learning outcomes in social studies learning in Pontianak Mujahidin Primary School. The method used was experimental with an unequal Pre-Experimental Design and control group design. The population of all students from two classes is 72 people. the sample of this study was class IIID students which amounted to 35 people as an experimental class and class IIIE as a control class totaling 37 people. Data collection techniques used are measurement techniques and data collection tools are multiple choice written tests. Based on data analysis, the average results of the post-test experimental class were 82.67 and the average post-test control was 77.09. Hypothesis test results using t-test (Polled Variance) obtained t count = 3.394 while for degrees of freedom (35 + 37-2 = 70) with a significant level ? = 5% obtained t table = 1.669, which means t count> t table Hal this proves that there is an impact of the Picture and Picture model in social studies learning. Based on the results of the effect size calculation (ES) obtained ES = 0.56 which includes the medium criteria. Keywords:   Impact,  Picture and Picture, Learnin Outcomes, Learning Sciences